5 kajian kaidah dalam ushul fiqh - Nadiroh, Ummi (Maliki Interdisciplinary Journal, 2024)
In fact, the fears of Muslims were formulated by early classical scholars through the science of fiqh Ushr and the science of fiqh rules. Fiqh, and the science of Fiqh rules.Istinbas Islamic Law has 4 important sciences that are interrelated. The first two are the "basic sciences", namely Fiqh and Ushul-Al-Fiqh. The science of fiqh is concerned with the actions of the mukhallaf, and in this connection is divided into obligatory, sunnah, haram, makruh and permissible. Ushr al-Fiqh, on the other hand, functions as a methodology. It is both a methodology and a measure of the accuracy of Istinbas. Ushr Fiqh is in charge of determining the procedures for legal istinbas. steps. Given the modern world, modern problems arise and of course modern thinking must seek modern thinking to find the answer. In this case the rules of fiqh as a discipline that is able to provide answers to various contemporary problems. disciplines that can provide answers to various modern problems occur.